Keberhasilan Jangka Panjang Ablasi Radio Frekuensi Takikardia Right Ventricular Outflow Tract - Hauda El Rasyid; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2013)
Background. Right Ventricular Outflow Tract (RVOT) tachycardia is frequentlyfound in clinical practice. Despite of its good prognosis no need itusually affects the reproductive age (20-40 years) and can be very symptomatic.Radio frequency ablation (RFA) is a recommended therapeuticoption of RVOT tachycardia. The aim of this study is to evaluate longtermresultsof RFA in National Cardiovasxular Center Harapan Kita.Method. A retrospective cohort study conducted to subjects with RVOTtachycardia who underwent RFA during period of 2005-2011. Clinicalcharacteristics are revealed from medical record and electrophysiologycharacteristics are revealed from electrophysiology recording system(PruckaTMandWorkmateTM). ECG morphology assessed by 2 observersusing digimatic calliper MitutoyoTM. Patients that received pharmacologicaltherapy act as control group. All patients are observed up to 1 year.Results. Sixty two patients underwent RFA (mean age of 43,56 ± 11,77year,46 female). ECG morphologies are all left bundle branch blok (LBBB),inferior axis, transtitional zone ? V4. Based on ECG morphology, septal siteare majority of cases. Mean EA (earliest activation) is 41,26 ± 16,94 ms,median 39,50 ms. An acute successful rate of RFA is 79%.Long termsuccessrate is 83,9 % as compare to only 40,9% in medical therapy group(RRR77%, p=0.001). Septal origin site is an independent factor of success ofRFA RVOT tachycardia.Conclusion. RFA of RVOT tachycardia is safe and effective with betterlongterm result as compare to pharmacological therapy.